Associations between physicians' SDM behaviour and participation of older patients and family members in triadic decision-making: An observational study - Bea L. Dijkman; Marie Louise Luttik; Wolter Paans; Ellen M. Driever; Hanneke van der Wal-Huisman; Paul L.P. Brand; Barbara.L. van Leeuwen (Elsevier, 2024)
Background: Medical consultations with older patients often include triadic conversations and decision-making processes involving physicians, patients, and family members. The presence of family members may change the communication dynamics and therefore increase the complexity of the consultation and decision-making process. Objective: This study explored associations between physicians' shared decision-making (SDM) behaviour and patients' and family members' participation in the decision-making process. Methods: Using an observational design, we analysed 95 recorded consultations between medical specialists, patients aged ≥65 years, and accompanying family members at a Dutch hospital. The OPTIONMCC was used to assess the physicians' SDM behaviour and patients' and family members' levels of involvement in SDM. Results: We found a strong positive correlation between physicians' behaviour and patients' and family members' participation in SDM (0.68 and 0.64, respectively, p < .01). Family members were more involved in SDM for patients aged 80 and older. Conclusion: While not asserting causation, our study suggests physicians potentially play a facilitating role in shaping the SDM process together with proactive contributions from patients and family members. Innovation: The results offer new insights into triadic SDM and provide suggestions for refining the OPTIONMCC. Further research is recommended into participants' mutual directional influences in triadic SDM.